Antibiotics' Use in Thailand: Community Pharmacists' Knowledge, Attitudes and Practices - Budh Siltrakool; Ilhem Berrou; David Griffiths; Saleh Alghamdi (MDPI AG, 2021)
Thailand spends $203 million on antibiotics every year, and patients can still access antimicrobials over the counter without a prescription. Community pharmacy plays a pivotal role in improving access and ensuring the appropriate use of antimicrobials. However, little is known about current practices in this setting. This study aims to assess Thai community pharmacists' knowledge, attitudes and practices (KAP) regarding antimicrobials' use and resistance. A cross-sectional study was conducted in Bangkok and Chonburi province in 2017 using an online self-administered questionnaire. The questionnaire was completed by 372 community pharmacists (71.4% response rate). The most commonly encountered infections in the community were upper and lower respiratory tract infections. The most commonly dispensed antimicrobials were broad-spectrum antibiotics including aminopenicillins and fluoroquinolones. Thai pharmacists have a good knowledge, attitude, and practice regarding antimicrobials' use and resistance. They dispense anti-microbials in line with local guidelines, although international guidelines may not indicate anti-biotics for viral self-limiting infections. While community pharmacy in Thailand could be the most accessible healthcare resource for patients, inappropriate provision of antimicrobials for self-limiting viral infections by pharmacists will increase antimicrobial resistance. This highlights the need for updated guidance and improved pharmacists' training.